2012
DOI: 10.4049/jimmunol.1200019
|View full text |Cite
|
Sign up to set email alerts
|

Ras Oncoproteins Transfer from Melanoma Cells to T Cells and Modulate Their Effector Functions

Abstract: Lymphocytes establish dynamic cell–cell interactions with the cells they scan. Previous studies show that upon cell contact, various membrane-associated proteins, such as Ras-family proteins, transfer from B to T and NK lymphocytes. Mutations in RAS genes that encode constitutively active, GTP-bound, oncoproteins are rather common in human cancers; for instance, melanoma. Cancer immunoediting has been postulated to contribute to the elimination of malignant melanoma. Thus, we asked whether Ras oncoproteins can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Interestingly, previous reports suggest that inner plasma membrane (PM)-anchored Ras proteins can transfer from antigen-presenting B cells to T cells both through the immunological synapse and through actin supported long-range PM extensions termed tunneling nanotubes. These findings further support the importance of Ras GTPases in immunity, by showing that active Ras-GTPase signals can spread between immune cells (12, 13) and even from cancer cells expressing oncogenic Ras to T cells (14). …”
Section: Introductionsupporting
confidence: 66%
“…Interestingly, previous reports suggest that inner plasma membrane (PM)-anchored Ras proteins can transfer from antigen-presenting B cells to T cells both through the immunological synapse and through actin supported long-range PM extensions termed tunneling nanotubes. These findings further support the importance of Ras GTPases in immunity, by showing that active Ras-GTPase signals can spread between immune cells (12, 13) and even from cancer cells expressing oncogenic Ras to T cells (14). …”
Section: Introductionsupporting
confidence: 66%
“…12, 23, 25 We have previously validated this observation regarding the transfer of GFP-H-Ras from B721.221 cells to NK cells 12 as well as from melanoma transfectants to T cells. 27 In these studies, by immunofluorescence staining with anti-Ras mAbs, we found a positive correlation between the immunostaining and the amount of GFP-H-RasG12V acquired by the T cells only in permeabilized cells – but not in intact cells. Moreover, our previous 12, 27 and present findings show that GFP-H-RasG12V is primarily distributed in the PM of the adopting T cells.…”
Section: Discussionmentioning
confidence: 66%
“…27 In these studies, by immunofluorescence staining with anti-Ras mAbs, we found a positive correlation between the immunostaining and the amount of GFP-H-RasG12V acquired by the T cells only in permeabilized cells – but not in intact cells. Moreover, our previous 12, 27 and present findings show that GFP-H-RasG12V is primarily distributed in the PM of the adopting T cells. Taken together, all these multimodality data suggest that the transferred GFP-H-RasG12V is in fact incorporated into the inner aspect of the PM of the adopting T cells and signals to induce the phosphorylation of its downstream effector ERK1/2.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Such connections allow the transfer of membrane-anchored proteins, plasma membrane (PM) fragments, and even microRNAs 1 - 5 . This “unorthodox” intercellular information transfer occurs through various incompletely defined mechanisms.…”
mentioning
confidence: 99%